THE CONCEPT OF MODERNISM BY MYKOLA YEVSHAN AND DMYTRA DONTSOV AND THE CREATIVITY OF MARK CHEREMSHYNA: IDEOLOGICAL AND AESTHETIC REFLECTIONS - Bagan, Oleg (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article studies the problem of ideological and aesthetic resonance between the theoretical reflections of Ukrainian essayists and estheticians Mykola Yevshan (1889 – 1919) and Dmytro Dontsov (1883 – 1973) and the artistic work of the modernist writer Mark Cheremshina. It will suffice that both theorists were influenced by the philosophical ideas of French intuitionism and German irrationalism (spiritual-historical school). They developed the aesthetic principles of literary neo-romanticism in Ukrainian literary studies. The main aesthetic concepts of M. Yevshan and D. Dontsov are "spiritual power", "energy of words", "element of feelings", "dynamism", "irrational", "optimism", "tragic", "heroic". Therefore, they sharply criticized European and Ukrainian decadentism, formalism in creativity, egocentrism of modernists. Relaxed, aesthetic, spiritually closed modernism was opposed by art energetic, strong in spirit, highly problematic, heroic-tragic in content. The prose of Mark Cheremshina in the interpretation of D. Dontsov as a continuation of the aesthetic line of M. Yevshan seemed to him to be close to the prose of the Norwegian writer Knut Hamsun. He undermined Cheremshina's imposed definition of "impressionist" as too superficial. In essence, he saw M. Cheremshina as a neo-romantic, although he did not use this aesthetic concept. He emphasized the great energy of his words, the optimism of his feelings, ethnic organicity.